Profile of the Intervention Potential of the Phylum Actinobacteria Toward Quorum Sensing and Other Microbial Virulence Strategies - Sarveswari, Hema Bhagavathi; Solomon, Adline Princy (Frontiers in Microbiology, 2019)
The rapid dissemination of antimicrobial resistance amongst microorganisms and their deleterious effect on public health has propelled the exploration of alternative interventions that target microbial virulence than viability. In several microorganisms, expression of virulence factors are co-ordinately controlled by quorum sensing systems. A comprehensive understanding into microbial quorum sensing systems, virulence strategies and pathogenesis have exposed potential targets, whose attenuation may alleviate infectious diseases. Such virulence attenuating natural products sourced from the different phyla of bacteria from diverse ecosystems have been identified. In this review, we discuss chemical entities derived from the phylum Actinobacteria, that have demonstrated the potential to inhibit microbial biofilms, enzymes, and other virulence factors both in vivo and in vitro. We also review Actinobacteria-derived compounds that can degrade quorum sensing signal molecules, and the genes encoding such molecules. Since many Actinobacteria-derived compounds have been translated into pharmaceutically important agents including antibiotics, the identification of virulence attenuating compounds from this phylum exemplifies their significance as a prospective source for anti-virulent drugs.